Substance use : individual behavior, social interactions, markets and politics - Lindgren, Björn, 1942-; Grossman, Michael, 1942- (Advances in health economics and health services research ;, 2005)
"The economics of substance use and abuse deals with the consumption of goods that share two properties. First, they are addictive in the sense that an increase in past consumption of the good leads to an increase in current consumption. Second, their consumption harms the consumer and others. This second property makes them of interest from policy, legal, and public health perspectives. The tremendous expansion in research in the economics of substance use and abuse since the early 1980s and the presence of many unresolved issues motivate this volume. While most of the papers are by economists, the disciplines of medicine, political science, and psychology also are represented. Any successful attempt to address substance use must adopt an interdisciplinary perspective. The aim of the volume to cover issues pertaining to individual behaviour, social interactions, markets, and politics makes this all the more necessary."--Jacket